The effect of COVID-19 lockdowns on women's perinatal mental health: a systematic review. Issue 1 (February 2023) - Wall, Stephanie; Dempsey, Maria
Abstract: Background: Risk factors for poor maternal perinatal mental health include a previous mental health diagnosis, reduced access to perinatal services, economic concerns and decreased levels of social support. Adverse maternal perinatal mental health can negatively influence the psychological wellbeing of infants. The outbreak of the COVID-19 pandemic presented an additional stressor. While literature on the impact of COVID-19 on perinatal mental health exists, no systematic review has focused specifically on maternal perinatal mental health during periods of COVID-19 lockdown. Aims: This systematic review explores how periods of COVID-19 lockdown impacted women's perinatal mental health. Methods: Searches of CINAHL, PsycARTICLES, PsycINFO, PubMed, Scopus and Web of Science were conducted for literature from 1st January 2020–25th May 2021. Quantitative, peer-reviewed, cross-sectional studies published in English with perinatal women as participants, and data collected during a period of lockdown, were included. Data was assessed for quality and narratively synthesized. Findings: Sixteen articles from nine countries met the inclusion criteria. COVID-19 lockdowns negatively impacted perinatal mental health. Risk factors for negative perinatal mental health noted in previous literature were confirmed. In addition, resilience, educational attainment, trimester, and ethnicity were identified as other variables which may influence mental health during perinatal periods experienced during lockdown. Understanding nuance in experience and harnessing intra and interpersonal support could advance options for intervention. Conclusion: Developing resources for perinatal women that integrate informal sources of support may aid them when normal routine is challenged, and may mediate potential long-term impacts of poor perinatal maternal health on infants.